All‐in‐One Bioinspired Multifunctional Graphene Biopolymer Foam for Simultaneous Removal of Multiple Water Pollutants. Issue 18 (9th August 2020) - Yap, Pei Lay; Hassan, Kamrul; Auyoong, Yow Loo; Mansouri, Negar; Farivar, Farzaneh; Tran, Diana N. H.; Losic, Dusan
Abstract: Polluted waters are complex systems with many different co‐existing contaminants that make their simultaneous removal a very challenging task. To address this problem, all‐in‐one ad/ab‐sorbent with unique combination of interfacial properties and multiple surface chemistry is developed to simultaneously and efficiently remove several pollutants including heavy metals, dyes, oils, and organic solvents. By mimicking the wetting micro‐topology of a darkling beetle with a combined hydrophilic‐hydrophobic surface, a new bioinspired adsorbent, graphene biopolymer foam (Alg‐Fe3 O4 ‐rGO‐4S) for removal of multiple water pollutants is engineered by combining alginate (Alg) and reduced graphene oxide (rGO) functionalized with tetrathiol that is also decorated with iron oxide nanoparticles (Fe3 O4 ). This concept is first proved by single pollutant removal, showing adsorption capacity of 789.7 ± 36 mg/g for methylene blue (MB), 107.0 ± 2.1 mg/g for Hg (II), 73.5 ± 0.7 mg/g for Cu (II), and rapid oil‐water separation with high sorption capacity (11–18 g/g). A remarkable performance for simultaneous removal of their mixtures in milli‐Q, river, and sea water is demonstrated with efficiency for MB (≈90%), Cu (II) (>99.99%) and Hg (II) (100%) and rapid (≈30 s) uptake of organic solvents and oils. The obtained results indicate a valuable potential of proposed concept for simultaneous removal of co‐existing water pollutants. Abstract : Multifunctional graphene biopolymer foam (Alg‐Fe3 O4 ‐rGO‐4S) with combined biomimetic hydrophilic‐hydrophobic feature is developed using photoinitiated functionalization by tetrathiol thiol–ene click chemistry that endows the modified foam with unique interfacial, surface, and structural properties for remarkable simultaneous removal of multiple pollutants from waters such as: heavy metal ions, cationic dyes, oils, and organic solvents.